Proceedings of the 7th International Driving Symposium on Human Factors in Driver Assessment, Training, and Vehicle Design : Dr 2013
DOI: 10.17077/drivingassessment.1472
|View full text |Cite
|
Sign up to set email alerts
|

Human Factors Issues Associated with Limited Ability Autonomous Driving Systems: Drivers’ Allocation of Visual Attention to the Forward Roadway

Abstract: Summary: This study characterized driver behavior and established a foundation for defining functional performance requirements associated with a Limited Ability Autonomous Driving System (LAADS) -a system capable of automated steering and speed/headway maintenance tasks on freeways, but does not relieve drivers of all driving tasks. The research was designed to examine and reveal potential issues associated with the use of semi-autonomous systems, exploring impacts on willingness to engage in secondary non-dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 5 publications
5
63
0
Order By: Relevance
“…For example, it has been experimentally found that people are inclined to watch DVDs in a highly automated car (Carsten, Lai, Barnard, Jamson, & Merat, 2012;Llaneras, Salinger, & Green, 2013). Furthermore, over 30 driving simulator studies have measured a reduction of self-reported workload in sophisticated driving simulator studies, (see De Winter, Happee, Martens, & Stanton, 2014, for a review), which matches the results of our questions regarding task difficulty (Q25-27).…”
Section: Discussionsupporting
confidence: 58%
“…For example, it has been experimentally found that people are inclined to watch DVDs in a highly automated car (Carsten, Lai, Barnard, Jamson, & Merat, 2012;Llaneras, Salinger, & Green, 2013). Furthermore, over 30 driving simulator studies have measured a reduction of self-reported workload in sophisticated driving simulator studies, (see De Winter, Happee, Martens, & Stanton, 2014, for a review), which matches the results of our questions regarding task difficulty (Q25-27).…”
Section: Discussionsupporting
confidence: 58%
“…Carsten and colleagues (Carsten, Lai, Barnard, Jamson, & Merat, 2012) found that engagement in non-driving tasks, like reading or usage of a DVD player, increased from manual to highly automated driving as a substitution for the vehicle control task. Llaneras, Salinger and Green (2013) reported similar results with engagements like eating or e-mailing. Summed up, engagement in a non-driving task is very likely in highly automated driving.…”
Section: Engagement In a Non-driving Task As Use Case In Highly Automsupporting
confidence: 62%
“…Beyond that, it is also possible that the system might require a transfer to Level 2 if the conditions necessitate it (Creaser & Fitch, 2015). An automated driving system will allow the driver to take his eyes off the road and engage in NDRTs and driving simulator studies show that drivers are willing to do so, possibly increasing the demand of a take-over situation (Carsten, Lai, Barnard, Jamson, & Merat, 2012;Llaneras, Salinger, & Green, 2013;Radlmayr, Gold, Lorenz, Farid, & Bengler, 2014). This act of reliance is only performed if the driver trusts driving automation enough to completely hand over the driving task.…”
Section: The Role Of Trust In Automated Drivingmentioning
confidence: 99%